Demonstration of Spin Current Switch across Ferro‐Antiferromagnetic Transition. Issue 10 (2nd September 2020) - Zhang, Yi‐Hui; Weng, Ting‐Wei; Chuang, Tsao‐Chi; Qu, Danru; Huang, Ssu‐Yen
Abstract: The first‐order magnetic phase transition between antiferromagnetic (AFM) and ferromagnetic (FM) states around room temperature is one of the unique features in FeRh. More fascinating is that the phase‐transition temperature ( T tr ) can be readily modulated by the magnetic field. In this work, a spin current valve is isothermally demonstrated by electrically and thermally probing the spin channel during the phase transition. When switching between the AFM and FM states, a large magnetoresistance ratio of 50% is obtained. Meanwhile, the on/off ratio for the magnetospin‐polarized thermal voltage associated with the magnonic spin current can be nearly infinite. It is shown that the significantly modulated T tr and switching critical field in FeRh advance its potential applications for the spin current switch devices. Abstract : The electrically and thermally excited spin current is utilized to probe the first‐order magnetic phase transition between antiferromagnetic and ferromagnetic states in FeRh. The spin current valve is isothermally demonstrated by tuning temperature or magnetic field during the first‐order phase transition, by which the on/off ratio of spin current induced by the anomalous Nernst effect is nearly infinite.